6a+6=4a-1

Simple and best practice solution for 6a+6=4a-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a+6=4a-1 equation:


Simplifying
6a + 6 = 4a + -1

Reorder the terms:
6 + 6a = 4a + -1

Reorder the terms:
6 + 6a = -1 + 4a

Solving
6 + 6a = -1 + 4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4a' to each side of the equation.
6 + 6a + -4a = -1 + 4a + -4a

Combine like terms: 6a + -4a = 2a
6 + 2a = -1 + 4a + -4a

Combine like terms: 4a + -4a = 0
6 + 2a = -1 + 0
6 + 2a = -1

Add '-6' to each side of the equation.
6 + -6 + 2a = -1 + -6

Combine like terms: 6 + -6 = 0
0 + 2a = -1 + -6
2a = -1 + -6

Combine like terms: -1 + -6 = -7
2a = -7

Divide each side by '2'.
a = -3.5

Simplifying
a = -3.5

See similar equations:

| 3x-2+4x+x+12=66 | | 12x^2+18=30 | | mp+mq=r | | 3(x-4)=2(x-3) | | 21x-6+5=26 | | 5v-9=3v+1 | | 3(5-5)= | | 88=7x+5x+4 | | -12x+7=4x-9 | | 7v-9=4v+3 | | 81t^2-144t+64= | | 5(2+t)-2(t+1)= | | 6v-4=5v+4 | | 16s^2-56s+49= | | b=75+(15+6)w | | (-2xy^2)(3x^2y^4)= | | x(x+7)=120 | | v-5/3-v=-3(v-1) | | 8n-(6n+5)=7 | | 190-2x+x+10=180 | | 2x-1=y | | 2x+10=y | | 4+4x/3=6 | | 2x-13=y | | -3x+5=y | | 3x+6=33 | | 13=-3x-8 | | (3x-1)(x+4)= | | 2y-6y+8=2(-2y+9) | | 10x^2-20=-5x | | 4x+9-y= | | 10(y-3)=5(y+5) |

Equations solver categories